Focal Vibration Therapy: Vibration Parameters of Effective Wearable Devices - Mustafa Ghazi; Josiah Rippetoe; Raghuveer Chandrashekhar; Hongwu Wang (Applied Sciences, 2021)
Focal vibration therapy can provide neurophysiological benefits. Unfortunately, standardized protocols are non-existent. Previous research presents a wide range of protocols with a wide range of effectiveness. This paper is part of a broader effort to identify effective, standardized protocols for focal vibration therapy. In this study, the authors evaluated the vibration characteristics (frequency and peak-to-peak intensity) of four commercially available focal vibration devices: (1) Vibracool (wearable), (2) Novafon (hand-held), (3) Myovolt 3-actuator (wearable), and (4) Myovolt 2-actuator (wearable). An accelerometer was used for the measurements. Measurements were made under the following two conditions: (a) when the devices were free, i.e., unconstrained vibration, and (b) when the devices were strapped to the human body, i.e., constrained vibration. In the free vibration condition, frequency ranged from 120 to 225 Hz and peak-to-peak amplitude ranged from 2.0 to 7.9 g’s. When the devices were strapped to the body (constrained), vibration amplitude decreased by up to 65.7%. These results identify effective ranges of focal vibration frequency and amplitude. They illustrate the importance of identifying vibration environment, free or constrained, when quoting vibration characteristics. Finally, the inconsistency output of multi-actuator devices is discussed. These results will guide protocol development for focal vibration and potentially better focal vibration devices.